Noise Sensitivities in Dogs: An Exploration of Signs in Dogs with and without Musculoskeletal Pain Using Qualitative Content Analysis - Lopes Fagundes, Ana Luisa; Hewison, Lynn; McPeake, Kevin J.; Zulch, Helen; Mills, Daniel Simon (Frontiers in Veterinary Science, 2018)
Noise sensitivity is a common behaviour problem in dogs. In humans, there is a well-established relationship between painful conditions and the development of fear-related avoidance responses. Whilst it is likely that a relationship exists between noise sensitivity and pain in dogs, this does not appear to have been investigated. The aim of this study was to explore the signs of noise sensitivity in dogs with and without musculoskeletal pain by comparing case histories using qualitative content analysis. Data were extracted from the clinical records of 20 cases of dogs presenting with noise sensitivity seen by clinical animal behaviourists at the University of Lincoln, composed of 2 groups—10 “clinical cases” with pain and 10 “control cases” without pain. Loud noises as a trigger of noise sensitivity were a common theme in both groups but ubiquitous among “clinical cases.” In “clinical cases” (i.e., those where pain was identified), the age of onset of the noise sensitivity was on average nearly 4 years later than “control cases.” In addition, strong themes emerged relating to widespread generalisation to associated environments and avoidance of other dogs in the “clinical cases,” which did not appear in the “control cases.” “Clinical cases” responded well to treatment once the involvement of pain had been identified. Veterinarians and behaviourists should carefully assess dogs with noise sensitivities for pain-related problems especially if presenting with these characteristics.